溫裏藥인 附子, 乾薑, 肉桂, 吳茱萸의 면역조절효과 비교 - 손길현(Gil Hyun Son); 신상우(Sang Woo Shin); 권영규(Young Kyu Kwon); 김상찬(Sang Chan Kim); 박종현(Jong Hyun Park) (동의생리병리학회지, 2005)
This study was carried out to investigate the comparison of immunomodualtory effects of water-extracted Aconiti Iateralis Preparata Radix(PR), Zingiberis Rhizoma(ZR), Cinnamomi Cortex(CC) and Evodiae Fructus(EF). The parameter examined to assess apparent immunomodulatory effect of the water-extracted PR, ZR, CC and EF included the regulation of Nitric oxide (NO). Also, ZR and EF represent the expression of Th1/Th2 type cytokine, the change of B cell phenotype. The water-extracted PR, ZR, CC and EF inhibited NO production and iNOS protein expression in LPS stimulated RAW 264.7 macrophage cells. In the Th1 and Th2 cytokine expression, the water-extracted ZR and EF induced IL-2, IFNr and IL-10 mRNA gene expression. Therefore, it seems that the water-extracted ZR and EF have a inducing effect of Th1 and Th2 type cytokines. In the Flow cytometry analysis, the water-extracted ZR and EF changed B cell phenotype (CD45R/B220), did NOT in PR and CC. The water-extracted PR, ZR, CC and EF have a reducing effect of immune suppression cause by Methotrexate (MTX), an agent of immune suppression. These results suggest that the immunomodulatory effects of the water-extracted ZR and EF may be, in part, associated with the inducing IL-2 and IFNr mRNA gene expression in and regulation of NO production in macrophage cells. KCI Citation Count: 0